Identification of new peloteopic loci conferring resistance to Leaf Rust and Yellow Rust in wheat on chromosome 1B in "Arabelu" and "Mucuy" populations - CGIAR Research Program on Wheat (2020)
Genomic region is identified with flanking markers KASP markers need to be developed